Sosialisasi Retribusi Parkir pada Juru Parkir di Kota Lamongan - Mokhtar Sayyid; Rina Sulistyowati; Dwi Sartika; Slamet Priyanto (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2020)
Parking fees are a potential source of local revenue (PAD). Revenue from parking fees is a potential source of local revenue, given the fact that there has been an increase in the number of motorized vehicles in Lamongan Regency, both cars and motorbikes. The problem with parking fees that is often faced is a lack of understanding about parking fees and law enforcement related to parking fees. Based on these problems, the community service team of Institut Teknologi dan Bisnis Ahmad Dahlan in collaboration with the Lamongan Regency Government held a socialization of parking fees for parking attendants in Lamongan Regency with the hope that there would be an increase in understanding of parking fees and their laws, followed by an increase in Regional Original Revenue (PAD) so as to create development growth in Lamongan Regency.